190k views
5 votes
5 (3x+4)-2x=7x-3 (-2x+11) help

User Gigadot
by
8.6k points

2 Answers

7 votes
Step one: multiply and divide in order. Step two: add and subtract like terms. Step three: get X alone on one side (what you do to one side you have To do to the other side) Step four: simplify and solve :)
User OnePunchMan
by
8.2k points
5 votes
first×5×3×=15×
2nd 5×4=20
so 15x+20-2x= 13x+20 and the other side of the equation is 7
multiply -3×-2x=6x
multiply -3×11=-33
now rewrite equation
13x+20=6x-33
get values to left side and numbers to right side
13x-6x= -33-20 or 7x = -53
now ÷ by 7 x=8 6/7
User Robotcookies
by
8.0k points